Pretransplant Fasting Glucose Predicts New-Onset Diabetes after Liver Transplantation - Elizabeth J. Carey; Bashar A. Aqel; Thomas J. Byrne; David D. Douglas; Jorge Rakela; Hugo E. Vargas; Adyr A. Moss; David C. Mulligan; K. Sudhakar Reddy; Harini A. Chakkera (Journal of Transplantation)
New-onset diabetes after transplantation (NODAT) is common after liver transplant and associated with poorer outcomes. The aim of this study was to identify risk factors for NODAT in liver transplant recipients off corticosteroids. In 225 adult nondiabetic liver transplant recipients, the mean age was 51.7 years, the majority were men (71%), and half had HCV (49%). The mean calculated MELD score at transplantation was 18.7, and 19% underwent living-donor transplant (LDLT). One year after transplantation, 17% developed NODAT, and an additional 16% had impaired fasting glucose. The incidence of NODAT in patients with HCV was 26%. In multivariate analysis, HCV, pretransplant FPG, and LDLT were significant. Each 10 mg/dL increase in pretransplant FPG was associated with a twofold increase in future development of NODAT. The incidence of NODAT after liver transplant in patients off corticosteroids is 17%. Risk factors for developing NODAT include HCV and pretransplant FPG; LDLT is protective.